Analisis Fenomena Doomscrolling pada Mahasiswa Perspektif Hadis tentang Pemanfaatan Waktu - Siti Rosyidatul Abidah; Nasrulloh (Al-Kindi, 2026)
This study aims to analyze the phenomenon of doomscrolling among university students from the perspective of hadith on time management. This research uses a qualitative-descriptive method with an empirical approach and thematic hadith study. Empirical data were obtained through written responses from students who actively use social media, while the thematic hadith approach was used to examine hadiths related to free time, youth, accountability of life, and leaving what is not beneficial. The findings show that doomscrolling among students often begins with ordinary activities such as seeking entertainment, following recent news, or reading online comments, but gradually develops into repetitive consumption of negative content. This habit affects students’ attention, emotional condition, rest time, and academic responsibilities. From the hadith perspective, doomscrolling reflects the need for awareness in using time responsibly. The relevant hadiths emphasize that free time and youth are valuable blessings, human life will be held accountable, and Muslims are encouraged to leave matters that bring no benefit.